Données conscernant la limitation de la salissure microalgale sous l’action de quelques substances antivégétatives - Bodeanu, Nicolae (Cercetări Marine - Recherches Marines, 2026)
Tests regarding the action of some anti-vegetative substances on the development of algal microfouling from sea submerged metallic plates have been carried out by the biological method of qualitative and quantitative analysis. The taxonomic composition of micro-algo-fouling, being made of particularly by Pennate Diatoms, was established. Some substances have been found to present a high degree of toxicity. The anti-vegetative substances demonstrate a selective toxic impact on different microphytes algal species.